'Prepped for prison'? Experiences of exclusionary school practices and involvement with the justice system. Issue 3 (December 2022) - Liston, Lindsey
Internationally, the link between punitive school disciplinary practices and increased risk of contact with the justice system has been chronicled via a substantial body of research on the school-to-prison pipeline. This research highlights some of the harmful effects of exclusionary school discipline for some students, including lower educational achievement, lower school completion rates and future contact with the justice system. Drawing on some of the findings from 50 in-depth interviews with former prisoners, educators, parents, and a range of key stakeholders, this paper builds on that research by identifying the informal ways that some groups of students are subjected to exclusion in schools. The findings suggest that to fully understand the factors that impact the path from school to involvement with the justice system, greater attention should be paid to the experience of informal school-based exclusionary practices.